2015
DOI: 10.3109/14767058.2015.1118033
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude of pregnant women toward flu vaccination: a cross-sectional survey

Abstract: Overall, knowledge regarding influenza, implications during pregnancy and influenza vaccine was poor among pregnant women. In Italy, the National Vaccine Prevention Plan 2012-2014 recommends influenza vaccine during pregnancy, but only 18/309 were aware of this recommendation. These results suggest that in order to increase influenza vaccine acceptance it is necessary to improve pregnant women knowledge about influenza and to offer education to healthcare providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 19 publications
2
22
0
1
Order By: Relevance
“…community or hospital-based practitioners) is the most influential. Similar to the quantitative literature, qualitative studies have shown that a recommendation by an HCP was not always sufficient [26,34,36,41,45,46,62,63,67]. Reasons for refusal despite HCP recommendation from the qualitative analysis provide insights into the effects of fear, mistrust, and a feeling of accountability [61,63,67,73,75].…”
Section: Discussionmentioning
confidence: 82%
“…community or hospital-based practitioners) is the most influential. Similar to the quantitative literature, qualitative studies have shown that a recommendation by an HCP was not always sufficient [26,34,36,41,45,46,62,63,67]. Reasons for refusal despite HCP recommendation from the qualitative analysis provide insights into the effects of fear, mistrust, and a feeling of accountability [61,63,67,73,75].…”
Section: Discussionmentioning
confidence: 82%
“…As different Italian's authors showed, this high vaccination refusal is similar by the time. For example, Fabiani et al and Rizzo et al investigated influenza vaccine uptake during 2009 A/H1N1 pandemic outbreak, finding coverage rates of 2% and 4%, respectively; more recently (2017), Maurici et al and Napolitano studied immunization in pregnant women in two cross‐sectional studies conducted, respectively, in Rome and Naples: all the women recruited by Maurici were unvaccinated, while Napolitano et al found an hesitancy reaching more than 80% in their sample.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, women with higher knowledge regarding the usefulness of the vaccination are more willing to receive the vaccine during pregnancy [2729] and the uptake is influenced by the low perception of the risks related to influenza [17, 20, 30, 31]. To date, there has been very little research concerning the level of knowledge and behaviors regarding seasonal influenza and the associated factors among pregnant women in Italy [32]. Therefore, the present survey was performed to achieve two primary objectives.…”
Section: Introductionmentioning
confidence: 99%